Laporan Kasus: Petekie pada Rongga Mulut Akibat Faktor Iatrogenik pada Pasien Anak - Helmi Hirawan; Fanni Kusuma Djati; Eliska Reza Mulitasari (Fakultas Kedokteran Gigi Universitas Jember, 2020)
Petechiae are round red lesions with a diameter of less than 2 mm located in the subcutaneous tissue or submucosa. Locations that often occur are the buccal mucosa, cheeks, lips, lateral tongue, base of the tongue, palate, oropharynx. The etiologic factors of petechiae consist of two types, local factors and systemic factors. Local factors that cause petechiae such as trauma, injury, fellatio, iatrogenic trauma. Systemic factors that cause petechiae such as platelet abnormalities, blood clotting factor disorders, blood vessel damage. An 8-year-old woman with her parents came to RSGMP Unsoed with complaints of red spots on the floor of the mouth, the patient was not aware of the redness under the tongue before treatment on the right lower tooth, did not feel pain and did not feel disturbed by this condition, The patient stated that this had never happened before. The patient is undergoing dental pulpotomy. Petechiae caused by trauma can heal by eliminating the etiologic factor.